2009
DOI: 10.1038/nature07864
|View full text |Cite
|
Sign up to set email alerts
|

Virus-free induction of pluripotency and subsequent excision of reprogramming factors

Abstract: Reprogramming of somatic cells to pluripotency, thereby creating induced pluripotent stem (iPS) cells, promises to transform regenerative medicine. Most instances of direct reprogramming have been achieved by forced expression of defined factors using multiple viral vectors1-7. However, such iPS cells contain a large number of viral vector integrations1,8, any one of which could cause unpredictable genetic dysfunction. While c-Myc is dispensable for reprogramming9,10, complete elimination of the other exogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
748
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,143 publications
(766 citation statements)
references
References 27 publications
5
748
0
13
Order By: Relevance
“…To meet this need, several nonintegration systems and removable systems have been developed. These include episomal vectors (Yu et al, 2009), the piggyBac transposon system (Kaji et al, 2009;Woltjen et al, 2009;Yusa et al, 2009), and minicircle vectors (Jia et al, 2010).…”
Section: Viral-free Approaches That Do Not Cause Genetic Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet this need, several nonintegration systems and removable systems have been developed. These include episomal vectors (Yu et al, 2009), the piggyBac transposon system (Kaji et al, 2009;Woltjen et al, 2009;Yusa et al, 2009), and minicircle vectors (Jia et al, 2010).…”
Section: Viral-free Approaches That Do Not Cause Genetic Alterationmentioning
confidence: 99%
“…Although iPSCs can be obtained by removable transposon or the non-integration episomal system, all of these methods still involve introducing foreign DNA into the cell so that the resulting cell lines need to be sequenced to verify that they are indeed free of genome alteration (Kaji et al, 2009;Woltjen et al, 2009;Yu et al, 2009). Thus, a reprogramming approach that does not use any DNA is highly desirable.…”
Section: Generation Of Ips Cells Using Proteins or Mrnas Of Defined Fmentioning
confidence: 99%
“…Additionally, inducible systems have been developed to better control transgene expression [7]. Novel methods requiring no viral integration have also been developed [8][9][10][11][12], as have strategies using small molecules to promote reprogramming efficiency [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the viral vectors after integration with the host may lead to unexpected genetic disorder (Okita et al 2007;Takahashi et al 2007;Tateishi et al 2008;Yu et al 2009). Therefore, new and improved methods of generating iPS cells, including minimal or no genetic modification are needed (Huangfu et al 2008;Kaji et al 2009;Okita et al 2008;Stadtfeld et al 2008;Woltjen et al 2009;Yu et al 2009;Zhou et al 2009). Tateishi et al (2008) reported that iPS cells derived from human skin fibroblast by retroviral expression of OCT4, SOX2, c-MYC, and KLF4 have the potential to differentiate into insulin-producing islet-like clusters (ILCs).…”
Section: Differentiation Of Induced Pluripotent Stem Cellsmentioning
confidence: 99%